Estandarización del proceso workover de la empresa colombiana Independence a partir de la optimización de consumo de combustible (2020)
This document presents the process carried out for the standardization of pipe extraction and insertion times of the Workover process of the Colombian company Independence to improve production. Independence identifies that there are significant differences in the operation of the process depending on different factors such as the operators, the day, weather conditions, among others. Among the controllable factors, are the person who operates the motor and therefore, it is carried out from the calculation of the recommended speed of the traveling block according to the load of the hook in the raising stage of the same in the POOH process (extraction of pipeline). Also, the initial position and uniformity of braking in the lowering stage of the traveling block is found according to the load of the traveling block in the RIH process (pipe insertion). One of the requirements is the operation of the engine in the range of minimum...